Use of applying aerobics classes at the recreational focus on basketball - Boyko A.L; Anikeenko L.V; Efremenko V.N; Mischuk D.N (Kharkov National Pedagogical University, 2010)
Raised the problem of optimizing the teaching process in physical education. 60 students took part in research. Proposed use of the author's method applied to the aerobics classes in basketball. This technique promotes the development of coordination abilities, flexibility, endurance, speed qualities. It used a combination of aerobics with the means of application and technical training for players, which include elements of the stands, bends, various movements. Also presented the structure of classes and their contents.